N‐Arylation of Fluoroalkylamine and Trifluoroacetamide through Cu–Catalysis. Issue 41 (5th November 2019) - Xin, Jiaqi; Leng, Faqiang
Abstract: Copper mediated coupling of fluoro‐alkylamines/trifluoroacetamide and aryl‐boronic acids have been developed. N‐arylation of di/trifluoroethylamine was achieved by a Cu(OAc)2 /Py system with AgNO3 as an additive, while the N‐arylation of trifluoroacetamide was described with Cu(OAc)2 /TEA system. These protocols could tolerate a variety of functional groups of hetero/aryl‐boronic acids, furnishing the corresponding products with moderate to good yields under mild and simple conditions. Abstract : Two simple and effective protocols to prepare N‐(fluoroalkyl/fluoroacetamide) aniline were developed. Various functional groups of aryl‐boronic acid were well tolerated. The selective of N‐arylation of fluoroalkylamine and fluoroacetamide was dramatically affected by the base.